2022
DOI: 10.18632/aging.204102
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of expression profiles and prognosis of TRIM genes in human kidney clear cell carcinoma

Abstract: Objective: To determine survival rates and the underlying mechanism of genes in the TRIM family in Kidney Clear Cell Carcinoma (KIRC). Methods: Transcriptional and survival data of TRIM genes in KIRC patients were retrieved from the UCSC Xena, and GEPIA databases. The function of TRIM genes in KIRC was investigated, focusing on potential ubiquitination, miRNAs regulation, and enrichment analysis. Next, TRIM gene survival values were determined, followed by the development of a survival-related signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, in Kidney Clear Cell Carcinoma (KIRC) Shen, Wang et al discovered that TRIM26 targets SNRBP, which directly participates in ubiquitination. This study reported shorter lifespan in patients with low levels of TRIM26 ( 22 ).…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, in Kidney Clear Cell Carcinoma (KIRC) Shen, Wang et al discovered that TRIM26 targets SNRBP, which directly participates in ubiquitination. This study reported shorter lifespan in patients with low levels of TRIM26 ( 22 ).…”
Section: Discussionmentioning
confidence: 63%
“…For miR-27b, Ishihara et al found that it functions as a tumor suppressor of RCC [42]. Hsa-mir-200b downregulation has been found to suppress metastasis of RCC [43], and hsa-let-7i has been implicated in RCC due to its relationship with TRIM genes [44]. Hsa-mir-24-1 plays a role in several different types of cancer [45] and may be connected to lupus nephritis [46].…”
Section: Discussionmentioning
confidence: 99%